Hindu Society’s Perception on Sharia Banking in Medan City - Ririn Khairiyah; Muhammad Yafiz; Nurlaila Nurlaila (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2022)
This study aims to explain the factors that influence the perception of Hindu people using Islamic banks in the city of Medan (Madras Hulu Subdistrict, Medan Polonia District) and also to find out the perception of hindus towards Islamic banking in the city of Medan. This study uses two free variables, namely religion, promotion and one bound variable, namely public perception. The sample used in this study was the Hindu community in Madras Hulu Village using a questionnaire as a data collection technique. The research approach carried out in this study is quantitative research with Multiple Linear Regression analysis supported by a normality test assisted by spss software version 26. From the results of the research conducted, the author concluded that socially religion has a positive and significant effect on people's perceptions, promotion has a positive and significant effect on people's perceptions. Religion and promotion together or simultaneously have a significant effect on perception. Religion and promotion were able to influence perception by 19.9% the remaining 80.1% explained by variables or other factors outside of the variables studied in this study.